Implementation of Procurement with Just in Time Method at the Stones Legian Bali Autograph Collection Hotels - Putri, Komang Ayu Trichia Maharani; Wiryanata, Wiryanata; Tuwi, I Wayan (Indonesian Journal of Banking and Financial Technology, 2024)
his study aims to determine the implementation of procurement with the just in time method in one of the hotels in Bali, namely The Stones Legian Bali Autograph Collection Hotels. The research method is descriptive qualitative using the stages of data reduction, data presentation and drawing conclusions. Data collection was carried out by interviews, documentation, and observation. The results of the study indicate that there are three stages of procurement of goods, in accordance with Wicaksono's theory, namely the purchasing stage there are users, culinary admins, executive sous chefs and purchasing who play a role in processing goods until the supplier receives the order. The second stage is receiving in the process of receiving goods. In the last stage, namely the storage and release of goods, at this stage the goods can be processed by each user outlet.